Diversity of Rare Tree Species in the Protected Forest of Tarakan Island - Nugroho, Bimo Aji; Fauzi, Ahmad; Umar, Hardianto S (Biopedagogia, 2024)
Since there is a dearth of information on the population of rare species in the Tarakan Island Protected Forest, this study intends to investigate the species diversity and distribution patterns of protected trees there. Determining the dominating rare tree species and the environmental factors influencing their distribution are among the issues that have been highlighted. The techniques involve statistical analysis to evaluate species diversity using the Shannon-Wiener index and field surveys to gather information on tree species, numbers, and habitat conditions. Five protected tree species with high levels of variety and balanced distribution—including Dipterocarpus cinereus and Intsia palembanica—were found in the results, demonstrating the resilience of the ecosystem. Climate, humidity, and soil quality are examples of abiotic variables that have a significant impact on tree development and spread. In summary, the occurrence of uncommon tree species is significantly influenced by the interplay between biotic and abiotic conditions, offering important information for Tarakan Island's biodiversity management and conservation. It is anticipated that this study will aid in the preservation of current natural resources.